Strategi Guru Bimbingan dan Konseling Dalam Mengatasi Perilaku Bullying di SMAIT Al-Madinah : Guidance and Counseling Teachers' Strategies in Overcoming Bullying Behavior at SMAIT Al-Madinah - Fachry Rizky Maulana; Retno Triwoelandari; Ikhwan Hamdani (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2025)
Basically, education plays an important role in shaping student behavior. In fact, the current condition of education is very worrying for all parties, both in the school environment and in daily life outside of school, problems often arise in relationships. Violence committed by students at school is bullying. Guidance and counseling are currently very much needed, especially in the world of education, because they function to deal with problems faced by students, one of which is bullying behavior. This research was conducted to find out 1) To find out the forms of bullying that occur at SMAIT AL-Madinah. 2) To find out the strategies of Guidance and Counseling teachers in dealing with bullying behavior that occurs at SMAIT Al-Madinah. 3) To find out the obstacles for Guidance and Counseling teachers in dealing with bullying behavior in class XI SMAIT Al-Madinah students. The research method used in this research is descriptive qualitative. This is because researchers want to know the strategies of guidance and counseling teachers in dealing with bullying behavior at SMAIT Al-Madinah. Researchers collect data directly from the field through observation, interviews and documentation. The analysis technique uses data reduction analysis, data presentation and conclusions. Based on the results of this research, it can be concluded as follows 1). The forms of bullying that occur at SMAIT Al-Madinah are verbal bullying, physical bullying and cyberbullying. This bullying behavior has a bad impact on both the victim and the perpetrator. The impact that occurs on victims of bullying is anxiety, fear and a feeling of wanting revenge. Meanwhile, the impact that occurs on bullies is that they think they are greater and cooler. 2). Guidance and counseling teachers' strategies for dealing with bullying behavior include implementing guidance and counseling services, collaborating with other parties and implementing a point system that applies to students.